Silencing of Soybean Raffinose Synthase Gene Reduced Raffinose Family Oligosaccharides and Increased True Metabolizable Energy of Poultry Feed - Valentine, Michelle F.; De Tar, Joann R.; Mookkan, Muruganantham; Firman, Jeffre D.; Zhang, Zhanyuan J. (Frontiers in Plant Science, 2017)
Soybean (Glycine max) is the number one oil and protein crop in the United States, but the seed contains several anti-nutritional factors that are toxic to both humans and livestock. RNA interference technology has become an increasingly popular technique in gene silencing because it allows for both temporal and spatial targeting of specific genes. The objective of this research is to use RNA-mediated gene silencing to down-regulate the soybean gene raffinose synthase 2 (RS2), to reduce total raffinose content in mature seed. Raffinose is a trisaccharide that is indigestible to humans and monogastric animals, and as monogastric animals are the largest consumers of soy products, reducing raffinose would improve the nutritional quality of soybean. An RNAi construct targeting RS2 was designed, cloned, and transformed to the soybean genome via Agrobacterium-mediated transformation. Resulting plants were analyzed for the presence and number of copies of the transgene by PCR and Southern blot. The efficiency of mRNA silencing was confirmed by real-time quantitative PCR. Total raffinose content was determined by HPLC analysis. Transgenic plant lines were recovered that exhibited dramatically reduced levels of raffinose in mature seed, and these lines were further analyzed for other phenotypes such as development and yield. Additionally, a precision-fed rooster assay was conducted to measure the true metabolizable energy (TME) in full-fat soybean meal made from the wild-type or transgenic low-raffinose soybean lines. Transgenic low-raffinose soy had a measured TME of 2703 kcal/kg, an increase as compared with 2411 kcal/kg for wild-type. As low digestible energy is a major limiting factor in the percent of soybean meal that can be used in poultry diets, these results may substantiate the use of higher concentrations of low-raffinose, full-fat soy in formulated livestock diets.